Effects of Bio-NPK Consortium on Growth, Yield and Nutrient Uptake by Rice under Clay Loam Textured Soil - V.H. Kadivala; R.P. Kacha, N.B. Gohil*, V.P. Ramani (Journal of the Indian Society of Soil Science, 2021)
Field experiment was conducted to see the effects of bio-NPK consortium on growth, yield and nutrient uptake by rice during kharif season of 2018 at Research Station, Anand Agricultural University, Thasra. The experiment was laid out in a randomized block design, comprising of twelve treatment combinations of different levels of iron (Fe) and zinc (Zn) with or without bio-NPK consortium (Azotobacter sp., Azospirillim sp. and Bacillus sp.) with three replications. The soil of Thasra experimental field was clay loam texture, medium in organic carbon, available nitrogen (N) and phosphorus (P), high in available potassium (K) and medium in available Zn and Fe. Results revealed that application of RDF + 75% Zn + 75% Fe + Bio-NPK consortium (T12) recorded significantly higher yield and uptake of N, P and S by rice grain and straw. The Fe content in straw and Zn content in grain increased significantly with application of RDF + 100% Zn + 100% Fe + Bio-NPK consortium (T10). Significantly higher Fe and Zn uptake by grain and straw of rice was observed with application of RDF + 75% Zn + 75% Fe + Bio-NPK consortium (T12). Maximum Cu uptake by rice straw was recorded with application of RDF + 100% Zn + 100% Fe + Bio-NPK consortium (T10). The available N, P, K, S, Zn, Mn and Cu content in soil after harvest of rice failed to show any significant influence with different treatments. Significantly higher available Fe (7.10 mg kg-1) in soil after harvest of rice was found in treatment with RDF + 75% Zn + 75% Fe (T11). Maximum population of Azotobacter, Azospirillum, phosphate solubilizing bacteria and potassium mobilizing bacteria in soil was found in treatment T12 (RDF + 75% Zn + 75% Fe + Bio-NPK consortium) over control.